LEAD USER IDENTIFICATION THROUGH TWITTER USING MICRO-BLOG DATA-A CASE STUDY IN THE AVIATION INDUSTRY - Schulz, Stefanie; Brem, Alexander; Gladysz, Bartosz (International Journal of Innovation Management, 2022)
To date, one of the most prominent methods to integrate users into the innovation process is the lead user method. However, due to its high resource intensity, it is less used than its potential would allow. In times of the internet and especially social media, this is changing since methods like netnography allow to efficiently identify potential lead users. Hence, based on a case study in the aviation industry, targeted screening and pyramiding are combined to identify lead users. Three users with sufficient characteristics to be lead users were included based on their degree-centrality and relevant contribution on Twitter. This study proposes the combination of these methods and Twitter as a suitable approach for lead user identification.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Lead user; open innovation; sticky information; user innovation